Role of Transarterial Angiography with Embolization in Deciding Surgical Approach to Juvenile Nasopharyngeal Angiofibroma: A Step-Ladder Approach - Manogaran, Ravi S.; Mathialagan, Arulalan; Singh, Vivek; Mishra, Prabhaker; Jain, Rajat; Keshri, Amit (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study was aimed to understand the usefulness of transarterial angiography and embolization in management of juvenile nasopharyngeal angiofibroma (JNA) and to apply the information obtained to stage the disease, select appropriate surgical approach, predict intraoperative bleeding, and prognosticate the disease.Study Design This study represents a retrospective review of the patients of JNA with major focus on transarterial angiography and embolization findings and its clinical and surgical implications.Setting The study conducted at a tertiary-care super-specialty referral center.Participants Forty-two patients who had undergone transarterial angiography and embolization followed by surgery over the period of 5 years from July 2015 till February 2019 were participated in this study.Main Outcome Measures Tumor vascular pattern based on transarterial angiography, staging of the disease based on extent and vascular supply, surgical approach selected, and prognosticating the disease were determined from this study.Conclusion Transarterial angiography with embolization becomes a prudent preoperative investigation for management of JNA. It provides a complete three-dimensional map of the tumor with stage-specific vascular pattern, reduces vascularity of the tumor, and predicts the sites from where bleeding can occur intra operatively. Thus, it helps in choosing the appropriate surgical approach aiding in complete tumor removal with minimal bleeding.
Keywords: juvenile nasopharyngeal angiofibroma; transarterial angiography and embolization; stage-specific vascular pattern; surgical approach for JNA